Estimating labour supply elasticities under rationing: a structural model of time allocation behaviour. - Prowse, V (2009)

(untitled)
This paper presents a structural model of the allocation of time to various non-market activities and market work by couples and single men and women. Parameters are estimated using a sample taken from the UK 2000 Time Use Survey. Own-wage effects are found to be positive for both men and women and are larger for cohabiting individuals than for singles. The presence of young children leads to a much larger increase in the time spent in home production by women than by men. However, the presence of young children causes men to increase their total time spent working by more than women.